The mediating role of spiritual leadership in the effect of organizational culture on organizational citizenship behavior - Hadi Purnomo; Christina Heti Tri Rahmawati; Tri Ratna Purnamarini; Ignatius Soni Kurniawan; M. Edhie Hartono (PHINISI, 2026)
Employee voluntary behavior or Organizational Citizenship Behavior (OCB) is highly needed by companies because it can encourage organizational progress and development in the future. Therefore, companies need to pay attention to various factors influencing OCB, one of which is organizational culture. A strong organizational culture is believed to shape positive employee behavior, including the willingness to contribute beyond formal job responsibilities. In addition, spiritual leadership is also considered an important factor in enhancing OCB, although its role as a mediating variable remains debated in previous studies. This study aims to examine the factors that encourage employees to demonstrate voluntary behavior or OCB. The study employed a quantitative approach using primary data obtained through questionnaires distributed to all employees of PT Catur Kencana Manajemen, involving 52 respondents through a census technique. Based on the testing results using SmartPLS, it was found that organizational culture and spiritual leadership have a positive effect on employees’ OCB.